Management of protective lung ventilation in children with a critical course of acute respiratory distress syndrome caused by SARS-CoV-2 coronavirus infection - Tkachuk , Roman (The Ukrainian Scientific Medical Youth Journal, 2024)
the pandemic of coronavirus disease COVID-19 has created a serious threat to the public health system worldwide. With the beginning of the pandemic, it became clear that children infected by SARS-CoV-2, for unknown reasons, have a milder course compared to adults. In some cases, children are asymptomatic carriers of the infection. In light of today's scientific discoveries, contrary to initial reports, recent studies have shown that children are just as likely to contract the virus as adults, while vague symptoms and a milder course more often characterize the disease itself. However, it is worth noting that the true prevalence of asymptomatic SARS-CoV-2 infection is most likely underestimated since children are not tested for COVID-19 without obvious clinical symptoms. This fact has been confirmed by multiple blood tests indicating high titers of IgG to SARS-CoV-2. Compared to adults, the typical clinical manifestations of COVID-19 in children are fever, runny nose, cough, and general weakness. The laboratory test results indicate a normal level of leukocytes, lymphopenia, and an increased level of aspartate aminotransferase, alanine aminotransferase, D-dimer, and MB creatine kinase. Currently, there is no sufficient evidence that the etiotropic therapy is 100% successful. Yet a course of action such as respiratory system protection, control of fluids and electrolyte homeostasis, anti-cytokine therapy, preventative measures for thrombosis, and treatment for bacterial superinfection proved to be efficient at preventing the development of possible complications caused by SARS-CoV-2. Therefore, it is important to collect and accumulate new experiences\cases of respiratory system protection management of an acute respiratory syndrome with a critical course of acute respiratory distress syndrome caused by COVID-19 and implement practical treatment plans for healthcare facilities. The results were analyzed using clinical epidemiology methods. Children were admitted to the intensive care unit on an average of 6,6±0,62 days of illness and were more associated with systemic disorders and water-electrolyte imbalance, which required prosthetic respiratory function, correction of hemodynamics and water-electrolyte disorders, which was carried out in the infectious diseases department of anesthesiology and intensive care for an average of 5,2±0,7 days. In children in the clinical group, SARS-CoV-2 was verified by reverse transcription polymerase chain reaction of a nasopharyngeal swab and/or exhaled air condensate based on its positive results. Comprehensive treatment of patients with severe and extremely severe respiratory distress syndrome in coronavirus disease included respiratory and hemodynamic support, antiviral and antibacterial therapy, parenteral glucocorticosteroids and anticoagulants, which was in line with current national regulatory guidelines and local protocols. According to the criteria for choosing a method of respiratory function prosthetics, in more than half of the patients (62,2%) with hemoglobin oxygen saturation of less than 92%, while maintaining active respiratory capacity, respiratory support was provided by supplementing humidified oxygen through a face mask or nasal cannulas. In another 29,7% of patients, non-invasive ventilation was performed by constant positive airway pressure, with an oxygenation index of 0,4-0,5 and a positive end-expiratory pressure of 4-5 cm of water column. Children who had a critical course of acute respiratory syndrome caused by coronavirus infection COVID-19 (8,1%) and in whom non-invasive methods of respiratory support did not bring the desired therapeutic result were on invasive ventilation in the mode of auxiliary controlled ventilation or in the mode of synchronized intermittent forced ventilation. It should be noted that children who received respiratory support in the form of non-invasive ventilation by means of constant positive airway pressure required a lower concentration of oxygen in the inhalation mixture compared to patients on free-flow oxygen supplementation. The need for admission to the intensive care unit of children with COVID-19 is primarily associated with respiratory disorders caused by interstitial pneumonia. Oxygen supplementation was of paramount importance in patient management, primarily through noninvasive ventilation with constant positive airway pressure or free flow. The use of a pulmonary protective strategy in the treatment of acute respiratory distress syndrome caused by coronavirus disease COVID-19 in children requiring invasive ventilation was accompanied by a pronounced positive result, as it was not accompanied by side effects and resulted in a rapid recovery of patients.